Comilla and U-J : a comparative study in rural developement policies - Manajure Maolā (Centre for Social Studies, 1980)
Comparative study of a project implemented by the Bangla Academy for Rural Development and the other at Ulashi-Jadunathpur, by the Bangladesh government.